Pelatihan Teknologi Pematangan Buah secara Alami bagi Pedagang Buah - Mohammad Wijaya; Sugiarti Sugiarti; sakinah zubair; Halimah Husain (Penerbit Widina, Widina Media Utama, 2024)
Fruit ripening is an important process that affects the quality and marketability of fruits. In this context, fruit traders often face challenges in ripening fruits in a natural and efficient way. This article discusses a training program that aims to provide training to fruit traders on natural fruit ripening technology. Through this approach, it is hoped that traders can improve the quality of their products and understand environmentally friendly methods. The training program included material provision, discussion and question and answer, and hands-on practice. The results showed that the training successfully gave the participants, who were fruit traders, a good understanding of natural fruit ripening. In addition, participants showed high enthusiasm during the training sessions, especially during discussions and questions and answers. The results of the participant satisfaction questionnaire analysis showed a positive assessment of various aspects of the training, with the highest average rating on the relevance of the material to the needs in the participants' environment. Thus, it is expected that this training will have a positive impact on participants, especially in terms of the quality of fruit produced from the ripening process. ABSTRAKPematangan buah adalah proses penting yang mempengaruhi kualitas dan nilai jual buah. Dalam konteks ini, pedagang buah sering kali menghadapi tantangan dalam mematangkan buah dengan cara yang alami dan efisien. Artikel ini membahas program pengabdian berupa pelatihan yang bertujuan untuk memberikan pelatihan kepada pedagang buah mengenai teknologi pematangan buah secara alami. Melalui pendekatan ini, diharapkan pedagang dapat meningkatkan kualitas produk mereka serta memahami metode yang ramah lingkungan. Program pelatihan meliputi pemberian materi, diskusi dan tanya jawab, serta praktik langsung. Hasil menunjukkan bahwa pelatihan berhasil memberikan pemahaman yang baik pada peserta yang merupakan pedagang buah dalam hal pematangan buah secara alami. Selain itu, peserta menunjukkan antusiasme yang tinggi selama sesi pelatihan, terutama saat diskusi dan tanya jawab. Hasil analisis angket kepuasan peserta menunjukkan penilaian positif terhadap berbagai aspek pelatihan, dengan rata-rata penilaian tertinggi pada keterkaitan materi dengan kebutuhan di lingkungan peserta. Dengan demikian diharapkan pelatihan ini memberi dampak positif bagi peserta khususnya dalam hal kualitas buah yang dihasilkan dari proses pematangan.